(untitled) (Journal of Dhaka Medical College, 2021)
Psoriasis is a common, chronic, immune mediated inflammatory disease that involves the innate immunological system (keratinocyte, dendritic cell, histiocytes, mast cells and endothelial cells) and acquired immunological system (T lymphocytes). Essential trace elements like iron (Fe), copper (Cu) undergo redox cycling and have physiological significance in inflammatory process. This study is aimed at measuring the level of copper, ceruloplasmin, iron and transferrin in psoriasis patient and to assess its relationship with the severity of the disease. This is an observational cross sectional study. It was conducted at the department of Dermatology and Venereology, BSMMU, Dhaka. Age range of the patient was 18 to 65 years. The mean age of the patients was 39.1±13.54 years, 57.9% patients were male and 42.1% were female. Male: female ratio was 1.4:1. Male patients were predominant. Mean duration of disease 5.36±4.05 years with range from 1.0 to 14 years. Most of the (76.3%) patients had mild disease followed by 23.7% had moderate to severe disease. Serum level of trace elements was compared between mild and moderate to severe group of psoriasis patients but difference were not statistically significant (p>0.05). Weak negative correlation was found between PASI score and serum levels of copper (r = “0.134, P = 0.423), iron (r = –0.080, p = 0.632), transferrin (r = –0.079, p = 0.638) and weak positive correlation was found with ceruloplasmin (r = 0.228, p = 0.168). The results of the present research provide valuable information and correlation between the measured biomarkers and severity of psoriasis. Serum Ceruloplasmin, copper, iron and serum transferrin could serve as a biomarker of psoriasis but not as a marker of psoriasis severity. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 59-68